Optically and remotely controlling localization of exciton-polariton condensates in a potential lattice - Ai, Qiang; Wingenbach, Jan; Yang, Xinmiao; Wei, Jing; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Ma, Xuekai; Gao, Tingge (Physical Review Applied)

Nebentätigkeiten von Lehramtsstudierenden während des Langzeitpraktikums: Lerngelegenheiten oder Belastungen? - Beckmann, Timo; Caruso, Carina; Homann, Hanna (Lehrerbildung auf dem Prüfstand)
There is currently a shortage of teachers in schools, which means that an increasing number of people without full qualifications are being employed. In the form of part-time work, students also take on jobs at schools that differ from those that are part of a long-term school internship in the teacher education pro gramme, as the long-term internship aims to professionalize prospective teachers, while part-time work is intended to alleviate any shortages. One condition for long-term internships to contribute to the profes sionalization of prospective teachers is the support of students by mentors and, associated with this, the intentional design and reflection of learning opportunities during the internship, which is not associated with meeting the needs of schools. It can be concluded that students who work in schools in the form of a part-time job alongside their long-term internship are confronted with a wide variety of role expectations and tasks, which can have an influence on their experience of stress, among other things. Based on a survey of students (n = 134), this article examines the extent to which students combine their long-term internship with part-time work, what tasks they have during this part-time work at school, how they are supported and to what extent they experience stress.

SemDial 2025 – Bialogue. Proceedings of the 29th Workshop on the Semantics and Pragmatics of Dialogue

“I'm Actually More Interested in AI Than in Computer Science” - 12-Year-Olds Describing Their First Encounter with AI - Lenke, Michael; Lehner, Lukas; Landman, Martina (2025 IEEE Global Engineering Education Conference (EDUCON))

Enhancing AI Interaction through Co-Construction: A Multi-Faceted Workshop Framework - Lenke, Michael; Schulte, Carsten (2025 IEEE Global Engineering Education Conference (EDUCON))

Émilie Du Châtelet on Time - Hagengruber, Ruth Edith (The Routledge Companion to Philosophy of Time)

The Dual Nature as a Local Context to Explore Verbal Behaviour in Game Explanations - Fisher, Josephine Beryl; Terfloth, Lutz (Proceedings of the 29th Workshop on the Semantics and Pragmatics of Dialogue (SemDial 2025))

Die (produktive) Rolle von generativer KI im erziehungswissenschaftlichen Diskurs - Herzig, Bardo (Erziehungswissenschaft. Mitteilungen der Deutschen Gesellschaft für Erziehungswissenschaft. Erziehungswissenschaft nach ChatGPT)

Higher Stakes, Healthier Trust? An Application-Grounded Approach to Assessing Healthy Trust in High-Stakes Human-AI Collaboration - Johnson, David S.
Human-AI collaboration is increasingly promoted to improve high-stakes decision-making, yet its benefits have not been fully realized. Application-grounded evaluations are needed to better evaluate methods for improving collaboration but often require domain experts, making studies costly and limiting their generalizability. Current evaluation methods are constrained by limited public datasets and reliance on proxy tasks. To address these challenges, we propose an application-grounded framework for large-scale, online evaluations of vision-based decision-making tasks. The framework introduces Blockies, a parametric approach for generating datasets of simulated diagnostic tasks, offering control over the traits and biases in the data used to train real-world models. These tasks are designed to be easy to learn but difficult to master, enabling participation by non-experts. The framework also incorporates storytelling and monetary incentives to manipulate perceived task stakes. An initial empirical study demonstrated that the high-stakes condition significantly reduced healthy distrust of AI, despite longer decision-making times. These findings underscore the importance of perceived stakes in fostering healthy distrust and demonstrate the framework's potential for scalable evaluation of high-stakes Human-AI collaboration.

Künstliche Intelligenz und professionsbezogene Aufgaben von Lehrkräften - Herzig, Bardo (SchulVerwaltung Bayern)

Team-Teaching angehender Lehrkräfte und Kompetenzen von Kindern im inklusiven naturwissenschaftlichen Sachunterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Einstellungen und prosoziales Verhalten von Grundschulkindern gegenüber Peers mit emotional-sozialem Förderbedarf im inklusiven Unterricht. Vortrag auf der Tagung der Kommission „Grundschulforschung und Pädagogik der Primarstufe“, Sektion Schulpädagogik, Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). Thema: „Bildung ohne Grenzen denken. Visionen der Grundschulbildung im europäischen Raum" - Löper, Marwin Felix; Hellmich, Frank

Exploring primary school teachers’ and special education teachers’ self-efficacy beliefs concerning inclusive education: A qualitative study. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Pauline; Schulze, Jan Roland; Hellmich, Frank

The role of teacher feedback for primary school students’ motivation and mathematical competencies. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Pre-service teachers’ professional self-concept development concerning team-teaching in primary schools. Paper. ECER 2025 (European Conference on Educational Research). “Charting the Way Forward: Education, Research, Potentials and Perspectives“ - Schulze, Jan Roland; Hellmich, Frank

Metaphors in 24 WIRED Level 5 Videos (Data corpus) - Scharlau, Ingrid; Miriam, Körber

Effects of a cooperation training on inclusion-related self-concepts of pre-service teachers. Poster Presentation. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Feedback as a predictor of primary school students’ motivation and mathematical competence. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Effects of parental feedback on children’s perceived feedback, motivation and achievement. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Knickenberg, Margarita; Hoya, Fabian Karl; Hellmich, Frank

Differences in pre-service teachers’ self-efficacy beliefs and willingness for inclusive education. Single Paper. The 21th Biennial EARLI (European Association for Research on Learning and Instruction) Conference on Learning and Instruction 2025. “Realising Potentials through Education: Shaping the minds and brains for the future” - Görel, Gamze; Franzen, Katja; Hellmich, Frank